PENGGUNAAN SITUS WEB HOTEL DAN “ONLINE TRAVEL AGENCY” SEBAGAI MEDIA PROMOSI DAN PENJUALAN BAGI HOTEL MELATI DI UBUD - Pande Putu Indrayana Tirtayasa; Syamsul Alam Paturusi (Magister Tourism Study, Faculty of Tourism, Udayana University, 2016)
The growth of the number of hotel rooms in Ubud has caused increasing business competition among the so called non-star melati hotel.Non-star melati hotel is a category of hotel which is not qualified to be awarded as a star hotel by Indonesian Ministry of Tourism.In response to the competition, the hotels embrace internet as a sales and promotion media by developing hotel websites.Individual tourism trend ignites the emergence of online travel agency websites (OTA) which used by tourists to compare and choose hotels thus increasing the importance of internet as a channel for selling and promoting hotel products.The purposes of this research are to identify motivation, perception, advantages and disadvantages of hotel website and OTA by non-star melati hotel operator’s perspective.Theories used are motivation, perception, and SWOT theory. Data was analyzed with descriptive qualitative method.Results show that hotel website and OTA have its own advantages and disadvantages. Motivation in using hotel website and OTA are very high.Perception in using hotel website and OTA are very agree. It is advised that hotels need to focus more on using OTA as source of getting guests, but also using hotel website, together as medium for promotion and sales activities.